Acute Respiratory Viral Infection in Children: Modern Approaches to Diagnosis and Treatment - Alexander A. Baranov; Yuriy V. Lobzin; Leyla S. Namazova-Baranova; Vladimir K. Tatochenko; Alexander N. Uskov; Tatiana V. Kulichenko; Maya D. Bakradze; Elena A. Vishneva; Liliia R. Selimzianova; Anastasia S. Polyakova; Inga V. Artemova; Elena A. Promyslova (Union of pediatricians of Russia, 2017)
The article is devoted to acute respiratory viral infections (ARVI) in children. ARVI take one of the leading places in a childhood morbidity structure. The article provides an overview of the clinical guidelines developed and approved by the professional association «Union of Pediatricians of Russia» for acute respiratory infections in children. These guidelines summarize the experience of the leading world and domestic specialists, contain scientific and practical data that correspond to the most relevant trends in the management of children with this pathology. The authors present modern information on the etiology, pathogenesis, classification, clinical findings and differential diagnosis of various nosological forms of acute respiratory tract infections in the pediatric population. The general (strategic) principles of drug-free and drug treatment are discussed in detail.